If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7z + 3) - (6z - 3) = 62
We simplify the equation to the form, which is simple to understand
(7z+3)-(6z-3)=62
Remove unnecessary parentheses
7z+3-(6z-3)=62
Remove unnecessary parentheses
7z+3-6z+3=62
We move all terms containing z to the left and all other terms to the right.
+7z-6z=+62-3-3
We simplify left and right side of the equation.
+1z=+56
We divide both sides of the equation by 1 to get z.
z=56
| 3(7x+9)-8(5x-2)=62 | | 2(x-1)+3-x=1+x | | 4x-2/3=1/2(x+3) | | (7x+3)-(6x-3)=15x+6 | | 4X^2-X-9=0 | | 18x-7=73-2x | | 7z+3-(6z-3)=15z+6 | | 2+3(2-x)=0.5x-2(x+2) | | 108-4x=32x+24 | | 16-2x+1=11 | | 3(7y+9)-8(5y-2)=62 | | 3x+x+2=x+20 | | 2x^2+7x-184=0 | | 25x+x^2=0 | | (7z+3)-(6z-3)=15z+6 | | 2x^2-13x-70=0 | | (7/15)x-(1/5)=4 | | 16-(2x+1)=11 | | 0.16*0.01(x+1)=-0.03(3-x) | | 12x^2-60x+7=0 | | 2(x-3)=3(x+7) | | 3x+(x+2)=x+20 | | -2x+5=-5x | | -17+2x=15 | | -5(3-x)=2x+7 | | 5(x-2)=2x | | 2(x+1)=3 | | 6-5x=2x+5 | | 3x^2+x=30 | | 3+0*x-1=2 | | 3*x-1=2 | | 0*x+4=-3 |